The Emergence of Minjung Theology and its Understanding of Reconciliation - Sang Hoon HAN (Program Pascasarjana UKIM, 2021)
This article aims to explore the theology of minjung. It is an accumulation and articulation of theological reflections on the political experience of Christian students, laborers, the press, professors, farmers, writers, and intellectuals as well as theologians in Korea in the 1970s. Minjung theology of Korea has been known as a branch of liberation theology. However, minjung theology was born in a special situation in Korea and has distinctive features from liberation theology. Through this research, I examine the definition, background, and characteristics of minjung theology, and attempts to research reconciliation, an important topic of modern theology, from the perspective of minjung theology. Minjung is economically poor, politically weak, socially deprived, but culturally and historically rich and powerful. Also, minjung, the poor, can think. They can do theology. There is no need for them to depend upon their oppressors to tell them what the gospel is.